Pelatihan Pembuatan Pembatas Buku Motif Barong di RT. 03 RW. 10 Kel. Jati Rangga Bekasi (Neolectura, 2023)
The Kranggan Traditional Stage House Community, Kranggan Wetan Village Rtt.03/010 Jati Rangga Village is very concerned about preserving kranggan culture, especially barong, whose existence is almost extinct. Barongan art craft training is motivated by the almost extinction of barong culture. Barong traditional art developed in the village of Kranggan is a traditional populist art that developed among the people and became part of the life of its supporting community. The art of the barongs of Kranggan village has been passed down from generation to generation by artists in the Bekasi area depicted in a pair of Barongs, who make up wearing a guise or mask with scary scary facial characters. To attract interest and motivate young youths who are members of the Kranggan traditional stilt house community, a learning stimulation is needed in the form of training in making barong arts. This training certainly can be a trigger for the enthusiasm of young people. By planning to implement the use of this training in the Kranggan Youth Organization environment, It is hope they grow love for and appreciate local cultural wisdom more..